THE RISK FACTORS FOR CARDIOVASCULAR DISEASE AMONG WORKER IN THE MINERAL MINING INDUSTRY - Dyan Kunthi Nugrahaeni; Muhtadi Muhtadi; Novie Elvinawaty Mauliku; Suhat Suhat; Gurdani Yogisutanti (Universitas Airlangga, 2026)
Introduction: The leading cause of illness and death worldwide is cardiovascular disease (CVD); of the 18.6 million CVD deaths worldwide, 35% happened in Asia. Among workers, specifically in the mining industry, CDV is a significant health issue impacting absenteeism and work productivity. Aims: to examine the cardiovascular disease risk factors among mineral mining sector workers, including hypertension, Type 2 Diabetes Mellitus (T2DM), dyslipidemia, obesity, and cigarette smoking. Methods: The design used a case-control study, with a sample case involving 200 respondents and a sample control are 200 respondents. Data collected from the medical record based on the examination results of the annual Medical Check-Up PT. Freeport Indonesia Hospital. Data analysis using chi-square test and binary regression logistic. Results: A risk factor for CVD were smoking a cigarette (p-value: 0.007, OR, 1.7, 95%: 1.16-2.57), hypertension (p-value: 0.002, OR, 2.61, 95%: 1.4-4.87), T2DM (p-value: 0.001, OR, 4.41, 95%: 2.78-7.01), dyslipidemia (p-value: 0.001, OR, 1.97, 95%: 1.31-2.97), and obesity (p-value: 0.001, OR, 2.07, 95%: 1.38-3.10). Conclusion: The risk factors for CVD are hypertension, T2DM, dyslipidemia, obesity, and smoking cigarettes. The recommendations for workers in the mineral mining industry suggested taking medication for hypertension, T2DM, dyslipidemia, and obesity treatment.